Risk factors for hidden blood loss in unilateral biportal endoscopic lumbar spine surgery - Guo, Sijia; Tan, Haining; Meng, Hai; Li, Xiang; Su, Nan; Yu, Linjia; Lin, Jisheng; An, Ning; Yang, Yong; Fei, Qi (Frontiers in Surgery, 2022)
Background: Unilateral biportal endoscopic (UBE) spinal surgery is a minimally invasive procedure for treating lumbar disorders. The hidden blood loss (HBL) is easily ignored by surgeons due to the less visible blood loss. However, there is limited study on HBL of UBE in spine surgery. The objective of this study was to evaluate HBL and its possible risk factors among patients undergoing UBE surgery. Methods: Patients with lumbar disc herniation or lumbar spinal stenosis undergoing unilateral biportal endoscopic surgery from December 2020 to February 2022 in our hospital were retrospectively analyzed. The patients' demographics, blood loss-related parameters, surgical and radiological information were collected. Pearson or Spearman correlation analyses were conducted to determine the association between clinical characteristics and HBL. Multivariate linear regression analysis was used to determine independent risk factors for HBL. Results: Fifty-two patients, 17 male and 35 female, were retrospectively enrolled in this study. The mean TBL was 434±212 mL, and the mean HBL was 361±217 mL, accounting for 77.9% of TBL in patients underwent UBE surgery. Multivariate linear regression analysis revealed that HBL was positively associated with operation time(P=0.040) and paraspinal muscle thickness of target level(P=0.033). Conclusions: The amount of HBL occurred in patients undergoing UBE surgery should not be neglected. The operation time and paraspinal muscle thickness of target level might be independent risk factors of HBL.